-3x + 4 = 7
-3x = 7 - 4
-3x = 3
x = -1
2006-11-06 12:25:00
·
answer #1
·
answered by matheson 2
·
0⤊
0⤋
1
2006-11-06 20:25:41
·
answer #2
·
answered by th_hunk 1
·
0⤊
0⤋
1
2006-11-06 20:24:52
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
x=1
2006-11-06 20:26:18
·
answer #4
·
answered by 7
·
0⤊
0⤋
3x+ 4 = 7
3x = 3
x=1
2006-11-06 20:26:38
·
answer #5
·
answered by Latina129 2
·
0⤊
0⤋
x= -1
2006-11-06 20:31:11
·
answer #6
·
answered by swim chick 3
·
0⤊
0⤋
3(1) + 4 = 7 therefore x = 1
2006-11-06 20:24:59
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
since we have:
-3x + 4 = 7
find x:
-3x + 4 = 7
-3x = 7 - 4 transpose 4 to the other side; change its sign
-3x = 3 simple subtraction
x= -1 divide both sides with -3; div prop of equality
2006-11-06 20:32:04
·
answer #8
·
answered by chem-o-phobic 2
·
0⤊
0⤋
3x+4=7
-4 -4
3x=3
x=1
2006-11-06 20:25:31
·
answer #9
·
answered by solls108 1
·
0⤊
0⤋
3x=3
x=1
2006-11-06 20:24:50
·
answer #10
·
answered by ceni40 3
·
0⤊
0⤋